Pre- and Post-M&A Financial Performance of Upstream Oil and Gas: Indonesia, Malaysia, Thailand - Praditya Dini Puspaningrum; Yasmine Nasution (Owner : Riset dan Jurnal Akuntansi, 2026)
The upstream oil and gas sector is experiencing intensifying pressures on firms and policymakers due to resource depletion, price volatility, and the global energy transition. In this environment, mergers and acquisitions (M&A) are widely pursued as strategic tools for portfolio optimization and reserve replacement. Therefore, it is necessary to empirically examine whether M&A activities generate significant improvements in the financial performance of acquiring firms in the upstream oil and gas industry. This study investigates whether M&A improves the firm-level financial performance of acquiring firms in the upstream oil and gas sector across Indonesia, Malaysia, and Thailand. It evaluates post-merger changes in profitability, liquidity, solvency, and shareholder value, offering comparative insights into whether M&A delivers measurable financial benefits for acquiring firms operating in the region’s capital-intensive energy industry. The study applies a structured pre–post event design using a six-year observation window, comparing three years of financial ratios before and after each M&A transaction while excluding the event year (T?). Financial and deal-level data for 34 upstream M&A events were triangulated from Rystad Energy, S&P Capital IQ, and official company reports, and analysed using descriptive statistics, the Wilcoxon Signed-Rank Test, the Mann–Whitney U Test and Regression with Clustered Robust Standard Errors (CRSE) to evaluate performance effects. The results reveal no statistically significant short-term improvement across profitability, liquidity, solvency, or shareholder-value ratios following M&A (p > 0.05). rofitability indicators remain largely unchanged except for a modest increase in GPM, while liquidity ratios are stable and solvency measures vary widely but with medians near zero. Shareholder-value metrics also exhibit minimal movement. Overall, early post-merger financial outcomes appear flat and uneven, indicating an absence of consistent short-term performance gains.